Understanding the Structural Elasticity of RNA and DNA: All‐Atom Molecular Dynamics. Issue 1 (8th September 2022) - Zhang, Yingtong; Yan, Miao; Huang, Tingting; Wang, Xianghong
Abstract: Nucleic acids play essential roles in some biological processes and nanotechnology. Understanding their structural elasticity is very important for biological functions. Differences in structural elasticity of RNA and DNA duplexes are investigated by all‐atom molecular dynamics in this work. Two models double‐strand (ds) B‐DNA and A‐RNA short sequences are used. For two typical sequences, bending persistence length, stretch, and twist modulus are analyzed and compared in detail. These results demonstrate that dsDNA has a smaller bending persistence length value than dsRNA, however, the former has about 2.6 times stretch modulus than the latter one and the twist modulus in the former is smaller than the latter. Furthermore, the microstructural parameter analysis indicates that the inclination angle of a single base pair and the dihedral angle between two bases in a base pair, as well as the slide between adjacent base pairs, influences the structural elasticities of these two types of nucleic acids. Results also show that the dsDNA has a positive stretch‐twist coupling parameter while the dsRNA has a negative stretch‐twist coupling parameter. Results offer research comprehensive comparing and understanding about structural elasticity of RNA and DNA and provide novel perspectives for grasping nucleic acids' elastic properties. Abstract : The structural elasticity of nucleic acids has been investigated by all‐atom molecular dynamic simulations. Based on the micro structural parameters analysis and conclusions of elastic parameters, quantitative elasticity conclusions are presented in detail here. The questions that have been bothering us that coupling dynamics of nucleic acids, some relationship also have been shown in this article.